Factors Raising the International Profile of Malaysia’s Medical Tourism - Yuaner, MA; Jabar, Juhaini Binti (International Journal of Psychosocial Rehabilitation, 2020)
Medical tourism has gained popularity in recent years as people across the world look to access less expensive or better quality medical treatment. It is growing so fast that many countries consider it as an emerging industry with the greatest development potential world-wide (Thomson Reuters, 2014). Based on a report conducted by SRI International, the world’s healthcare travel medical tourism revenue reached USD 678.5 billion in 2017, while this number was less than USD 10 billion in 2000. From 2013 to 2019, the global medical tourism industry maintained a compound annual growth rate of 17.9%, which is twice as much as that of the traditional tourism sector. According to a forecast of world health organization (WHO), by 2025, health services will become the world’s largest industry, and traditional tourism industry will be ranked second. The combination of two industries shall account for 22% of global GDP